Missed Appendicitis: Mimicking Urologic Symptoms. (26th December 2012) - Akhavizadegan, Hamed
Abstract : Appendicitis, a common disease, has different presentations. This has made its diagnosis difficult. This paper aims to present two cases of missed appendicitis with completely urologic presentation and the way that helped us to reach the correct diagnosis. The first case with symptoms fully related to kidney and the second mimicking epididymorchitis hindered prompt diagnosis. Right site of the pain, relapsing fever, frequent physical examination, and resistance to medical treatment were main clues which help us to make correct diagnosis.